Moderating Effect of Audit Report Timeliness on Audit Committee Attributes and Earnings Volatility of Quoted Oil and Gas Firms in Nigeria - Orijinta, Hope Ifeoma; Otiedhe, Gabriel Moses; Udoezika, Dave (PT. Riset Press International, 2025)
This paper evaluated the moderating effect of audit report timeliness on audit committee attributes and earnings volatility of quoted oil and gas firms in Nigeria from 2013 to 2022. Data were sourced from 10 quoted oil and gas multinationals. The study extracted data from the annual reports of the oil and gas firms. Meanwhile, the study adopted the moderated regression estimation technique. The study evidenced that audit committee financial expertise and the frequency of meetings reduce earnings volatility. However, audit committee independence increases earnings volatility due to stricter accounting practices imposed by independent members. The moderated regression analysis indicates that timely audit report issuance significantly mitigates the effect of audit committee effectiveness on earnings volatility. This implies that while an influential audit committee reduces earnings volatility, its impact is enhanced when audit reports are issued promptly. The study concludes that audit committee effectiveness and audit report timeliness are crucial for managing earnings volatility. Consequently, those with financial and industry experience should be encouraged to join the audit committee. Their expertise can help in better oversight and stabilization of earnings. Lastly, the management of sampled firms should develop a robust governance framework that integrates influential audit committee practices with timely audit reporting.